20. PREOPERATIVE ANXIETY AMONG PATIENTS UNDERGOING ELECTIVE SURGERY AT THE DEPARTMENT OF ANESTHESIOLOGY AND INTENSIVE CARE, TRANSPORT HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the prevalence of preoperative anxiety and its related factors among patients scheduled for elective surgery.Methods: A cross-sectional study was conducted on 85 patients (≥16 years) undergoing elective surgery at the Department of Anesthesiology and Intensive Care, Transport Hospital, from August 2024 to March 2025. Data were collected using a structured questionnaire and analyzed with SPSS 20.0.Results: The prevalence of preoperative anxiety was 56.5%. Higher anxiety was significantly associated with female gender (72.7%), no previous surgical experience (61.4%), and surgeries in Trauma (73.7%) and Obstetrics (71.4%) (p
Keywords: Preoperative anxiety; Elective surgery; Fear of pain